Developments in combined analgesic regimens for improved safety in postoperative pain management. (1st September 2020) - Pergolizzi, Joseph V.; Magnusson, Peter; Raffa, Robert B.; LeQuang, Jo Ann; Coluzzi, Flaminia
ABSTRACT: Introduction : Fixed-dose combination analgesic regimens may be similarly effective to opioid monotherapy but with potentially less risk. A number of individualized combination regimens can be created, including nonopioid agents such as acetaminophen and nonsteroidal anti-inflammatory drugs, opioids, and adjunctive agents such as gabapentin, pregabalin, and muscle relaxants. Areas covered : When such combinations have a synergistic effect, analgesic benefits may be enhanced. Many combination analgesic regimens are opioid sparing, which sometimes but not always results in reduced opioid-associated side effects. Safety concerns for all analgesics must be considered but postoperative analgesia is typically administered for a brief period (days), reducing risks that may occur with prolonged exposure. Expert opinion : Judiciously considered combination analgesic regimens can be effective postoperative analgesics that reduce opioid consumption without compromising pain control, which are important factors for patient recovery and satisfaction. The specific combinations used must be based on the patient, the type and duration of the surgical procedure, and complementary mechanisms of action of the agents used. In opioid-sparing combination analgesic regimens, the short-term use of small doses of opioids in this setting may be helpful for appropriate patients.